2011
DOI: 10.1007/s00431-011-1482-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of socioeconomic deprivation on efficacy of continuous subcutaneous insulin infusion: a retrospective paediatric case-controlled survey

Abstract: Parental educational deprivation was associated with a failure of MDI but not CSII therapy. These outcomes need confirmation by larger studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
2
12
0
Order By: Relevance
“…Similar to other studies linking socio‐economic status and metabolic control, our study demonstrated that this relationship may be partially mediated by differences in insulin regimen . We report that participants using insulin injection therapy had significantly lower NEI scores, on average, than those on pump therapy, and that the majority of pump users reside in neighbourhoods characterized by the least social inequity.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to other studies linking socio‐economic status and metabolic control, our study demonstrated that this relationship may be partially mediated by differences in insulin regimen . We report that participants using insulin injection therapy had significantly lower NEI scores, on average, than those on pump therapy, and that the majority of pump users reside in neighbourhoods characterized by the least social inequity.…”
Section: Discussionsupporting
confidence: 88%
“…Cultural barriers might lead to less-effective communication between healthcare providers and minority ethnic families, especially those that do not have English as their first language. Another explanation is the lower insulin pump use among minority ethnic and lower SES groups [27]. However, accounting for pump use only marginally attenuated the observed ethnicity estimates.…”
Section: Discussionmentioning
confidence: 93%
“…This might reflect a true biological difference, for example, haemoglobin glycosylation [14,15], or problem in engagement and understanding by healthcare professionals. The latter might also be an explanation for the lower pump therapy uptake, which has been suggested in other studies [16]. Alternatively, the cumulative stress that operates within certain ethnic groups might lead to alterations in allostatic load [17], which, by influencing cortisol secretion, would lead to differences in glucose regulation [18] and possibly views on health care and cognition [19].…”
Section: Discussionmentioning
confidence: 93%
“…The mean age was 10.6 years (range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], with an average duration of diabetes of 4.5 years. At each quarterly clinic visit, HbA 1c was measured, using the Siemens DCA1000 (Bayer) near-patient testing system (Siemens Healthcare Diagnostics Inc., Deerfield, IL, USA).…”
Section: Methodsmentioning
confidence: 99%